Pengembangan Pendidikan Islam Multikultural Berbasis Manajemen Sumber Daya Manusia: Development of Multicultural Islamic Education Based on Human Resource Management - Zain, Hefni (LP2M UIN KH.Achmad Siddiq Jember, 2013)
Although various measures of reform and development models for Islamic education have been initiated, these efforts have not yet fully achieved the expected goals. Empirically, the implementation of Islamic education in various educational units has not significantly impacted students' behavioral changes, even though one of its primary objectives is to transform their way of thinking, feeling, and worldview. The rise in moral decadence and undesirable behaviors such as violence, conflict, exclusivism, and weak tolerance and respect for others among school children indicates the ineffectiveness of current Islamic education models and functions. In response to these phenomena, the development of a multicultural Islamic education model is deemed essential, focusing on respect for diversity, pedagogical equality, and the elimination of discrimination to build a just, tolerant, democratic, humane, inclusive, and harmonious society regardless of ethnic, social, religious, or gender backgrounds. This study focuses on: (1) The concept of multicultural Islamic education development, (2) Its prescriptive and empirical foundations, (3) Opportunities and challenges in its development, and (4) Development based on human resource management. Meskipun telah dirintis berbagai langkah reformasi dan model pengembangan pendidikan Islam, upaya tersebut hingga kini belum sepenuhnya mencapai tujuan yang diharapkan. Pada ranah empiris, implementasi pendidikan Islam di berbagai unit pendidikan belum banyak memberikan implikasi signifikan terhadap perubahan perilaku peserta didik, padahal salah satu tujuan utama pendidikan Islam adalah perubahan pola pikir (way of thinking), perasaan (way of feeling), dan pandangan hidup (way of life) pada peserta didik. Fenomena meningkatnya dekadensi moral dan perilaku tidak terpuji seperti kekerasan, konflik, eksklusivisme, serta lemahnya toleransi dan penghargaan terhadap orang lain yang melibatkan anak sekolah menjadi indikator nyata ketidakefektifan model dan fungsi pendidikan Islam selama ini. Berdasarkan fenomena tersebut, pengembangan model pendidikan Islam multikultural dinilai penting untuk memfokuskan pada penghormatan terhadap keragaman, pengakuan kesetaraan pedagogis, serta penghapusan diskriminasi guna membangun masyarakat yang adil, toleran, demokratis, humanis, inklusif, dan harmonis tanpa memandang latar belakang etnik, status sosial, agama, atau jenis kelamin. Penelitian ini difokuskan pada: (1) Konsep pengembangan pendidikan Islam multikultural, (2) Landasan preskriptif dan empirik pengembangannya, (3) Peluang dan tantangan pengembangan, serta (4) Pengembangan berbasis manajemen sumber daya manusia.